The Analysis Of Musyarakah Contract Sharing System Implementationin BPRS Saka Dana Mulia Kudus - Nur Huda; Fitri Fajri (Universitas Islam Negeri (UIN) Walisongo Semarang, 2019)
Purpose - This research aims to know how the implementation of revenue sharing system to Musyarakah finance and to know the Conformity between the implementation done with Fatwa DSN No.08/DSN-MUI/IV/2000.Method - The study uses a qualitative descriptive approach with a type of case study research.Result - The results showed that a). the implementation of revenue sharing system to Musyarakah finance in BPRS Saka Dana Mulia uses projections or estimates between 1,75% - 2,5% multiplied by the bank's capital. This revenue sharing system has been determined at the beginning of the nominal magnitude of the result for which the customer must be deposited every month. But the bank continues to see the customer's business, when the customer's business suffered losses that are not caused by human error then the bank and the customer will renrenegotiate regarding the outcome.b). The implementation of Musyarakah finance to PT. BPRS Saka Dana Mulia which has been adjusted to Fatwa DSN No.08/DSN-MUI/IV/2000 located at the statement of ijab qabul, contract object (capital, work, andloss), Operational costs and disputes. While that is still not appropriate, that is in the part of the object contract about the profit.Implication - This research is only researching in PT. BPRS Saka Dana Mulia Kudus.Originality - there are differences in the division of sharing system between theories and practices implemented in BPRS Saka Dana Mulia.